Bibliometric Analysis of the Role of the Regional Development Planning Agency in Regional Development Planning in Indonesia - Asti Amelia Novita (Universitas Merdeka Malang, 2025)
Bappeda (Regional Development Planning Agency) is a local government organization responsible for regional development planning with the regional head. In the preparation of regional development planning activities, a process that is not only limited to planning but also includes the monitoring and realization of development is needed. This research aims to find out what role Bappeda plays in regional development planning. The method used in this research is a quantitative method with bibliometric analysis with the help of VosViewer software. The data used in this research is secondary data, namely published journals in the Garuda database preserved by Kemdikbudristek. Bibliometric analysis is used to obtain a mapping from previous journals to determine the role of Bappeda in regional development planning. The results obtained show that there are three main keywords from the mapping results of bibliometric analysis that are interconnected, namely Bappeda, planning, and development. Each of these keywords has a relationship with other items, including policy planning, budget mapping, development implementation, musrenbang, good governance, and the preparation of regional planning documents. This shows that the broad role of Bappeda is to develop regional development planning, starting from musrenbang activities at the village and district levels and budget mapping to the preparation of regional planning documents such as the RPJPD, RPJMD, and RKPD. In addition, Bappeda also plays a role in activities after planning, namely monitoring the implementation of development and realizing the principles of good governance